The effects of strength training and endurance training order on running economy and performance - Doma, K.; Deakin, G. B. (Applied Physiology, Nutrition, and Metabolism, 2013)
This study examined the acute effect of strength and endurance training sequence on running economy (RE) at 70% and 90% ventilatory threshold (VT) and on running time to exhaustion (TTE) at 110% VT the following day. Fourteen trained and moderately trained male runners performed strength training prior to running sessions (SR) and running prior to strength training sessions (RS) with each mode of training session separated by 6 h. RE tests were conducted at baseline (Base-RE) and the day following each sequence to examine cost of running (CR), TTE, and lower extremity kinematics. Maximal isometric knee extensor torque was measured prior to and following each training session and the RE tests. Results showed that CR at 70% and 90% VT for SR-RE (0.76 ± 0.10 and 0.77 ± 0.07 mL/kg-0.75·m-1) was significantly greater than Base-RE (0.72 ± 0.10 and 0.70 ± 0.11 mL·kg-0.75·m-1) and RS-RE (0.73 ± 0.09 and 0.72 ± 0.09 mL/kg-0.75·m-1) (P < 0.05). TTE was significantly less for SR-RE (237.8 ± 67.4 s) and RS-RE (275.3 ± 68.0 s) compared with Base-RE (335.4 ± 92.1 s) (P < 0.01). The torque during the SR sequence was significantly reduced for every time point following the strength training session (P < 0.05). However, no significant differences were found in torque following the running session (P > 0.05), although it was significantly reduced following the strength training session (P < 0.05) during the RS sequence. These findings show that running performance is impaired to a greater degree the day following the SR sequence compared with the RS sequence.